An effective comparison protocol over encrypted data in cloud computing. (October 2019) - Jiang, Leqi; Cao, Yi; Yuan, Chengsheng; Sun, Xingming; Zhu, Xiaoli
Abstract: Privacy-preserving is one of the most important concerns of cloud computing users. Encryption guarantees data security but makes data processing less convenient. Although many calculations in ciphertext domain are supported by some cryptosystems, the magnitude relation comparison over encrypted data is still difficult to be solved. In this paper, we proposed a comparison protocol for secure cloud computing using homomorphic encryption and incomplete re-encryption. Homomorphic encryption enables the process of data with some basic mathematical operations to be securely outsourced to cloud servers. Incomplete re-encryption is a novel method proposed by us, it can support ciphertexts to be decrypted to new plaintexts which maintains the magnitude relation but no original plaintexts leaked. Two cloud servers are involved in our protocol, calculator is responsible for the homomorphic operations on ciphertexts, and when the magnitude relation between the results needs to be known, calculator will ask comparator for assistance. The security and performance analysis demonstrate the security and effectiveness of the proposed protocol.